Effects of heat treatment on calabrian pine (Pinus brutia ten.) wood - Saim Ates; Hakan Akyildiz, M.; Hasan Ozdemir (BioResources, 2009)
In this study, the effects of heat treatment on some physical, mechanical, chemical properties, and cellulose crystallinity of calabrian pine (brutia Ten.) were evaluated. Wood specimens were treated with heat under atmospheric pressure at three different temperatures (130, 180, and 230 oC) and two different time levels (2 and 8 h). Air-dry density (Dm), oven-dry density (D0), shrinkage (β), swelling (α), fiber saturation point (FSP), compression strength parallel to grain (σc//), bending strength (σb), modulus of elasticity (MOE) in bending, equilibrium moisture content (EMC), holocellulose, and alcohol solubility were decreased, whereas 1% NaOH solubility and lignin content were increased, depending on the heating temperature and time. Cellulose crystallinity of the samples was not changed significantly. 130 oC showed a minimal effect; on the other hand, 230 oC showed a maximum effect on all properties of the treated wood. That’s why, for the heat treatment process, 130 oC for 2 h should be applied in situations where mechanical properties such as modulus of elasticity, compression strength, bending strength, and hardness are important. However, 230 oC for 2 h should be used in situations where it is preferred to obtain favorable physical properties, such as density, shrinkage, swelling, and moisture content.
Keywords: FT-IR; Calabrian pine; Chemical properties; Physical; Mechanical; Heat treatment; Crystallinity; TP248.13-248.65; Biotechnology